Experimental Study of Dorema aucheri Extraction with Supercritical Carbon Dioxide - Kamyab Moghadas, Bahareh; Akbar Safekordi, Ali; Honarvar, Bijan; Fathi Kaljahi, Jamshid; Ali Vaziri Yazdi, Seyed (Asian Journal of Chemistry, 2012)
Dorema aucheri Boiss. is a native Iranian medicinal plant that is used as food. This plant is rich in flavonoids. Flavonoids are compounds found in fruits, vegetables and certain beverages that have diverse beneficial biochemical and antioxidant effects. This medicinal plant pose great benefits for human health. In this work the extraction of flavonoid compounds from this plant, with supercritical carbon dioxide, is studied. Using supercritical CO2 seems to be a promising and alternative process because of operating at low temperature and acceptable mass transfer rate with no solvent residual at the last product. The operating conditions are pressure between 15 to 20 MPa and temperature between 313 to 323 K. After analyzing the extracted products by GC and GC/MS, a-eudesmol (39.2 %) and d-cadinene (12.9 %) were the major bioactive flavonoid compounds in this plant. The optimum pressure, temperature and dynamic extraction time were also determined.